Pathological findings of traumatic acute respiratory distress syndrome in a domestic cat - Yuvida , Alya; Sentosa , Vinne Chandra; Fajriannisa , Sarah; Khairani , Shafia (ARSHI Veterinary Letters, 2025)
Case reports of acute respiratory distress syndrome (ARDS) in cats that occurs due to traumatic events have not been widely discussed. The results of a necropsy performed on a cat that was known to have experienced a traumatic event (run over by a motor vehicle) can provide an overview of the pathological findings of ARDS. The pathological findings from the necropsy results included the presence of pink rose-colored foamy fluid in the trachea, hemorrhage, and petechiae in the lungs, accompanied by blood accumulation in the pleural cavity (hemothorax). Acute brain damage due to the head region being run over by a motor vehicle, such that the head shape becomes asymmetrical, is also one of the main causes of death in this cat.